ANALISIS KONSEPTUAL PENGGUNAAN SELF-TALK MOTIVASIONAL DALAM PENDIDIKAN JASMANI DI SMAN 1 PARUNG - Sidqi, Fahmi Khairu; Paramitha, Sandey Tantra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
The aim of this research is to analyze motivational self-talk from these three indicators, namely self-confidence indicators, expressions of strength and anxiety control that are most trusted by class X students at SMAN 1 Parung to increase enthusiasm for learning. This research uses a quantitative descriptive method with a questionnaire distribution technique. The population of this research was class X students at State Senior High School (SMAN) 1 Parung, totaling 377 students. By taking samples using random sampling techniques, the required number of research samples was 79 students. The instrument used in this research was a self-talk questionnaire received from a journal entitled